2012
DOI: 10.2355/isijinternational.52.2019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Changes in Sulfur and Oxygen Concentration on Change in Nitrogen Concentration in Liquid Steel during CaO^|^ndash;CaSi Powder Blowing under Reduced Pressure

Abstract: In this paper, 1 500 kg scale experiments of CaSi mixed CaO powder top blowing onto the Al killed steel were carried out under reduced pressure. And the effects of CaSi alloy ratio in the mixture on reactions of desulfurization and nitrogen removal were examined. Aluminum decreasing rate decreased and rate constant of desulfurization and nitrogen removal increased with increasing CaSi mixing ratio to flux. It is supposed from the above that deoxidation and desulfurization reaction can simultaneously occur by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Most studies of the hot metal powder desulfurization process have focused on top injection metallurgy technology [10][11][12][13][14][15], while the study of multiphase behavior in the process of ladle bottom powder injection with electric field is few. In addition, it is extremely hard or impossible to measure experimentally the particle trajectories in metallurgical systems, so mathematical simulation become an important method to understand this process [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of the hot metal powder desulfurization process have focused on top injection metallurgy technology [10][11][12][13][14][15], while the study of multiphase behavior in the process of ladle bottom powder injection with electric field is few. In addition, it is extremely hard or impossible to measure experimentally the particle trajectories in metallurgical systems, so mathematical simulation become an important method to understand this process [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Both of the authors reported an equation for estimation of the chemical reaction rate constant to quantify the speed of chemical reaction of nitrogen removal at the interface based on their experimental results and moreover, they found that the denitrogenation can be described as a reaction of second order that indicates that the reaction rate is proportional to the square of concentration. To account for the variation in the content of surface‐active element, Numata et al carried out extensive experiments by blowing calcium and aluminum compound flux powder to create a time‐dependent ambient of oxygen and sulfur content under reduced pressure. The results showed that the rate of nitrogen desorption increases as the contents of oxygen and sulfur in liquid steel decrease.…”
Section: Introductionmentioning
confidence: 99%